Hubungan antara Keterlibatan Ayah dan Motivasi Berprestasi pada Mahasiswa UI dengan Urutan Kelahiran Sulung - Mitranti Anindya Ayu; Adhityawarman Menaldi; Nurul Arbiyah (Jurnal Ilmiah Psikologi MIND SET, 2016)
Achievement is one important issue in teenagers and father has an important role in the life of their children. This study focused on correlation between father involvement with achievement motivation aspects on hope for success and fear of failure, in firstborns whose study in UI. There are two instruments used, Reported Father Involvement Scale (RFIS), which is part of Father Involvement Scale (FIS) to measure father involvement, and Achievement Motives Scale-Revised (AMS-R), to measure both achievement motivation aspects. The participants are 206 students from 13 faculties and 1 study program in Universitas Indonesia. the results shown no significant correlation between father involvement with achievement motivation aspects on hope for success, and there is no significant correlation between father involvement and fear of failure aspect.